1233. An Automated E-mail Notification Systemic to Infectious Disease Specialists and Effect on the Management of Staphylococcal aureus Bacteremia in a Community Hospital setting. (26th November 2018) - Roe, Nicole; Wang, Michael; Douce, Richard
Abstract: Background: Staphylococcus aureus is the leading cause of community and healthcare-associated bacteremia and carries a high burden with a substantial mortality, ranging from 20 to 40 %. Evidence suggests infectious disease (ID) consultation improves mortality and adherence to the Infectious Diseases Society of America (IDSA) guidelines. Due to complications from a lack of ID consultation, a notification system consisting of automated e-mails to ID providers was implemented. The objective of this study was to review the impact of the automatic notification to ID consultants with positive blood culture results in a community hospital system. Methods: Cases of staphylococcus aureus bacteremia were identified from the microbiology database by at least one positive blood culture. The automated e-mail notification system was implemented in December 2014. ID providers were encouraged to verbally contact primary providers for positive results. Cases of bacteremia prior to implementation of the automated notification system were compared with those post-intervention. Patients under age 18 were excluded. Data gathered included mortality, re-admission rates, and compliance with IDSA guidelines. Results: There were no significant differences in inpatient mortality (9 vs. 18%, P = 0.180). 30-day mortality between the two groups (18 vs. 20%, P = 0.815). The 30-day readmission rate among surviving patients was reduced by 50% (40% vs. 19%, P = 0.014). Compliance with antibiotic duration in complicated bacteremia increased post-intervention (57% vs. 85%, P = 0.04). Conclusion: An automatic notification to ID specialists reporting patients with Staphylococcus aureus bacteremia led to improved compliance with IDSA guidelines regarding antibiotic duration and reduced re-admission rates. There was no effect on overall mortality. All authors: No reported disclosures.